Organokines and Exosomes: Integrators of Adipose Tissue Macrophage Polarization and Recruitment in Obesity - Wang, Yuan-Yuan; Wang, Ya-Di; Qi, Xiao-Yan; Liao, Zhe-Zhen; Mai, Yun-Ni; Xiao, Xin-Hua (Frontiers in Endocrinology, 2022)
The prevalence of obesity is escalating and has become a worldwide health challenge coinciding with the development of metabolic diseases. Emerging evidence has shown that obesity is accompanied by the infiltration of macrophages into adipose tissue, contributing to a state of low-grade chronic inflammation and dysregulated metabolism. Moreover, in the state of obesity, the phenotype of adipose tissue macrophages switches from the M2 polarised state to the M1 state, thereby contributing to chronic inflammation. Notably, multiple metabolic organs (adipose tissue, gut, skeletal muscle, and the liver) communicate with adipose tissue macrophages via secreting organokines or exosomes. In this review, we systematically summarise how the organokines (adipokines, gut microbiota and its metabolites, gut cytokines, myokines, and hepatokines) and exosomes (adipocyte-, skeletal muscle-, and hepatocyte-derived exosomes) act as important triggers for macrophage recruitment in adipose tissue and adipose tissue macrophage polarisation, thus providing further insight into obesity treatment. In addition, we also highlight the complex interaction of organokines with organokines and organokines with exosomes, revealing new paths in understanding adipose tissue macrophage recruitment and polarisation.